ChemInform Abstract: Uniting C1‐Ammonium Enolates and Transition Metal Electrophiles via Cooperative Catalysis: The Direct Asymmetric α‐Allylation of Aryl Acetic Acid Esters. Issue 40 (September 2016) - Schwarz, Kevin J.; Amos, Jessica L.; Klein, J. Cullen; Do, Dung T.; Snaddon, Thomas N.
Abstract: Allylmethane sulfonate as well as diverse aryl substituted allyl carbonates efficiently react with pentafluorophenyl 2‐arylacetates to form α‐allylated products in high yields and with very high enantiomeric excesses.